2020
DOI: 10.1177/0885328220947889
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of liraglutide-loaded Poly-N-(2-hydroxypropyl) methacrylamide/chitosan nanoparticles: Preparation, characterization, and pharmacokinetics

Abstract: The delivery of peptides or protein drugs via the oral route has always presented a significant challenge. Here, nanoparticles for the oral delivery of liraglutide are prepared. The nanoparticles are composed of the biodegradable carrier materials chitosan and poly-N-(2-hydroxypropyl) methacrylamide (pHPMA). In addition, CSKSSDYQC (CSK) and hemagglutinin-2 (HA2) are introduced into the particles to improve the in vivo bioavailability of liraglutide. The size of the nanoparticles is less than 200 nm, and the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
(32 reference statements)
1
7
0
Order By: Relevance
“…[263] Due to the drawbacks of conventional injectable insulin, nanomaterials carrying insulin for oral and pulmonary delivery have been developed. [264] In addition, anti-diabetic drugs, such as phytocompounds, [265] Metformin, [266] Dapagliflozin, [267] Empagliflozin, [268] Liraglutide, [269] Exenatide, [270] and Linagliptin [271] have been reported to use alginate, [272] chitosan, [272a,273] poly(lactic-co-glycolic acid) (PLGA), [274] dextran, [258,275] poly(alkyl cyanoacrylates) (PACA), lipid, [276] poly(lactic acid) (PLA), [277] micelle, [278] Niosome, [279] etc., as delivery systems. More strikingly, zinc oxide nanoparticle (ZnONP) itself has shown anti-diabetic effect.…”
Section: Nanomedicine For the Treatment Of Diabetesmentioning
confidence: 99%
“…[263] Due to the drawbacks of conventional injectable insulin, nanomaterials carrying insulin for oral and pulmonary delivery have been developed. [264] In addition, anti-diabetic drugs, such as phytocompounds, [265] Metformin, [266] Dapagliflozin, [267] Empagliflozin, [268] Liraglutide, [269] Exenatide, [270] and Linagliptin [271] have been reported to use alginate, [272] chitosan, [272a,273] poly(lactic-co-glycolic acid) (PLGA), [274] dextran, [258,275] poly(alkyl cyanoacrylates) (PACA), lipid, [276] poly(lactic acid) (PLA), [277] micelle, [278] Niosome, [279] etc., as delivery systems. More strikingly, zinc oxide nanoparticle (ZnONP) itself has shown anti-diabetic effect.…”
Section: Nanomedicine For the Treatment Of Diabetesmentioning
confidence: 99%
“…To better penetrate the mucus network and epithelial cell membrane, the size of the nanoparticles needs to be controlled below 200 nm. 29,30 In this study, the size of the nanoparticles met this requirement. As shown in Fig.…”
Section: Characterization Of Pptt-npsmentioning
confidence: 72%
“…The NPs maintained a neutral surface charge before and after coating with pHPMA, which is ideal to avoid the interaction of the particles with mucins. The authors also showed the nanosystem had a 2.5‐times higher liraglutide AUC (~3284 pg.h/mL) and B R (~10%) values, than oral free liraglutide in solution (AUC ~1298 pg.h/mL and B R ~4%) in normoglycemic mice (Shi et al, 2021). B R was calculated according to Equation (1).…”
Section: Nanosystems Platforms For the Oral Delivery Of Glucagon‐like...mentioning
confidence: 99%